Largely enhanced dielectric properties of TiO2-nanorods/poly(vinylidene fluoride) nanocomposites driven by enhanced interfacial areas - Pornsawan Kum-Onsa (Taylor & Francis Group, 2021)
In this work, nanocomposites consisting of TiO2-nanorods (TiO2-NRs) with less than 100 nm in size and poly(vinylidene fluoride) (PVDF) were prepared using a liquid-phase assisted dispersion and hot-pressing methods. At 1 kHz and 25 °C, the high dielectric permittivity of ∼66 and loss tangent of ∼0.03 can be obtained in the nanocomposite with a filler volume fraction of 0.5, which was higher than that of a neat PVDF matrix by a factor of 6. Dielectric permittivity of TiO2-NRs/PVDF nanocomposites not only highly increased with TiO2-NRs, but also almost independent of the frequency range of 102–106 Hz. The significant enhancement in dielectric permittivity is mainly attributed to the interfacial polarization at the interfaces of TiO2-NRs and PVDF, and semiconducting properties of TiO2-NRs. Among the various models used for rationalizing the dielectric behavior, the experimental dielectric data is in close agreement with EMT (n = 0.11) and Yamada models (n = 8).